IoT-based portable health monitoring device - Rustamov, Zaur (2022)
Almost all the people in the world have various kinds of health problems. These health issues and ilnesses mostly require immediate and continuous monitoring of patient data by measuring body temperature, pulse rate, blood oxygen saturation, and skin conductance. Previous works on this matter have used many methods for each of the mentioned measurements separately. In this study, single IoT-based portable health monitoring device will be introduced. Sensors measuring body temperature, pulse rate, blood oxygen saturation and skin conductivity will be jointly implemented in this project. A webpage for showing the measurement data has been created and patient data is stored in private cloud accounts that patients possess. Through this study, a combined IoT-based portable health monitoring device, while maintaining the idea of not hurting patients has been made available for making immediate and continuous monitoring of patient data available for everyone with different kinds of health issues.